Development of Wordwall-Based Interactive Learning to Improve Student Achievement in Lower Grade Picture Diagram Material School - Chaya Fathier, Shafarinie; Arni, Yusni; Khulaifatuzzahra, Ismi; Nova Rianti, Dea; Agustina Khoirunnisa, Tri (Journal of Practice Learning and Educational Development, 2026)
This research is motivated by the low level of students' understanding of diagram material caused by conventional learning and the minimal use of interactive learning media. The purpose of this study is to develop interactive learning media based on Wordwall and determine the level of feasibility and effectiveness in improving student learning outcomes on diagram material for second-grade elementary school students. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were 33 second-grade students of SDN 01 Tanjung Raja, while the object of the study was Wordwall-based learning media. Data collection techniques included observation, interviews, documentation, and learning outcome tests, then analyzed qualitatively. The results of this study showed that the results of the media validation test were 87% and the material validation test was 90%. Thus, Wordwall media can be an innovative learning media to improve the understanding of diagram concepts in elementary school students.